Viktor Vrbnjak (1934–2005) (University of Maribor Press, 2025)
The ninth volume of the collection Osebnosti (Personalities) focuses on the life, work, and legacy of Viktor Vrbnjak — a Slavic linguist, archivist, and historian who made a significant contribution to Slovenian historiography in the first half of the 20th century. Through his in-depth research and extensive knowledge of 19th- and early 20th-century Styria, as well as his exceptional understanding of the lives and work of numerous individuals who left their mark on political, cultural, and national history, Vrbnjak left a lasting scholarly imprint. The introductory section outlines the purpose of the publication, presents the initiative behind its release, and describes the acquisition of Vrbnjak’s personal legacy for the Manuscript Collection of the University of Maribor Library. The introduction is followed by three thematic sections: (1) a presentation of Vrbnjak’s life and work, including a bibliography; (2) two previously unpublished papers from his estate, now annotated and prepared for publication; and (3) memorial reflections written by four of Vrbnjak’s contemporaries and companions. Each chapter is enriched with photographic and documentary material from his personal archive or from the collections of institutions where Vrbnjak left a notable impact.